The frequency of metabolic syndrome in patients with acrochordons (Bangladesh Journal of Medical Science, 2017)
Objective: To investigate the frequency of metabolic syndrome (MetS) in patients with acrochordons.Materials and Methods: 102 patients with acrochordons and 76 controls were enrolled into the study. The presence of MetS was evaluated under the criteria NCEP-ATP III.Results and Discussion: Waist circumference (p